Upper Pleistocene Stratigraphy, Paleoecology, and Archaeology of the Northern Yukon Interior, Eastern Beringia. I. Bonnet Plume Basin - Hughes, O.L.; Harington, C.R.; Janssens, J.A.; Matthews, Jr., J.V.; Morlan, R.E.; Rutter, N.W.; Schweger, C.E. (ARCTIC, 1981)
New stratigraphic and chronometric data show that Bonnet Plume Basin, in northeastern Yukon Territory, was glaciated in late Wisconsinan time rather than during an earlier advance of Laurentide ice. This conclusion has important ramifications not only for the interpretation of all-time glacial limits farther north along the Richardson Mountains but also for non-glaciated basins in the Porcupine drainage to the northwest. The late Wisconsinan glacial episode in Bonnet Plume Basin is here named the Hungry Creek advance after the principal Quaternary section in the basin. Sediments beneath the till at Hungry Creek have produced well-produced pollen, plant macrofossils, insects, and a few vertebrate remains. The plant and invertebrate fossils provide a detailed, if temporally restricted, record of a portion of the mid-Wisconsinan interstadial, while the vertebrate fossils include the oldest Yukon specimen of the Yukon wild ass. Some of the mid-Wisconsinan sediments have also yielded distinctive chert flakes that represent either a previously unreported product of natural fracturing or a by-product of stone tool manufacture by human residents of Bonnet Plume Basin. In addition to presenting new data on these diverse but interrelated topics, this paper serves as an introduction to a series of reports that will treat in turn the Upper Pleistocene record of Bluefish, Old Crow, and Bell basins, respectively.